2012
DOI: 10.1007/s10384-012-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of infraorbital nerve enlargement on MRI imaging in clinical diagnosis of IgG4-related orbital disease

Abstract: If IONE is observed in a case of orbital lymphoproliferative disorders on MRI, then it is highly possible that such a case is IgG4-ROD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 7 publications
2
32
1
Order By: Relevance
“…However, some clinical features and orbital CT and MRI findings were similar to those of TAO, including bilateral disease with a chronic onset, multiple areas of muscle enlargement, increased orbital fat, lacrimal gland enlargement, the absence of orbital masses and sinus involvement (1,11,12). A substantial proportion of cases of idiopathic orbital pseudotumors (11) or infraorbital nerve enlargement (13) in fact represent ocular adnexal manifestations of IgG4-RD; such symptoms were not seen in our patient. Therefore, definitively discriminating between TAO and IgG4-RD is difficult, possibly because the conditions are closely associated, sharing common autoimmune mechanisms.…”
Section: Discussionsupporting
confidence: 54%
“…However, some clinical features and orbital CT and MRI findings were similar to those of TAO, including bilateral disease with a chronic onset, multiple areas of muscle enlargement, increased orbital fat, lacrimal gland enlargement, the absence of orbital masses and sinus involvement (1,11,12). A substantial proportion of cases of idiopathic orbital pseudotumors (11) or infraorbital nerve enlargement (13) in fact represent ocular adnexal manifestations of IgG4-RD; such symptoms were not seen in our patient. Therefore, definitively discriminating between TAO and IgG4-RD is difficult, possibly because the conditions are closely associated, sharing common autoimmune mechanisms.…”
Section: Discussionsupporting
confidence: 54%
“…Although many of the aforementioned imaging features overlap with those of IgG4-related diseases, certain features, such as lobulation of the margin and the lesional T2 signal intensity may be helpful in differentiating ocular adenxal IgG4-related diseases from orbital lymphomas because ocular adnexal IgG4-related diseases tend to show hypointensity on T2-weighted images and well defined margin without lobulation 8 9 11. In addition, a recent study suggested that infraorbital nerve enlargement in orbital lymphoproliferative disorders on MRI indicates a high probability of IgG4-related orbital disease 10. In our case series, only one patient showed bilateral infraorbital nerve enlargement with widening of the infraorbial foramina (figure 3E).…”
Section: Discussionmentioning
confidence: 99%
“…Extraocular muscles [6,10,17,36] and infraorbital and supraorbital nerve enlargements [8,9,17,[36][37][38] are also frequently diagnosed in cases of IgG4-related ophthalmic disease. Inflammatory lesions in adipose tissue [8] surrounding the optic nerve [17,34], and even in the lacrimal drainage system [39,40], occur less frequently.…”
Section: Discussionmentioning
confidence: 99%